Association between metabolic syndrome and knee osteoarthritis: A cross-sectional nationwide survey study - Byung Joo Lee; Seoyon Yang; Sara Kwon; Kyung Hyo Choi; Won Kim (Medical Journals Sweden, 2019)
Objective: To investigate the association of metabolic syndrome with the development of knee osteoarthritis. Design: Cross-sectional nationwide survey study. Subjects: Data obtained from the 2010-2012 Korea National Health and Nutrition Examination Survey. Methods: Subjects aged 50 years or older were included. Knee osteoarthritis (≥grade 2 Kellgren-Lawrence) and severe knee osteoarthritis (≥grade 3 Kellgren-Lawrence) were evaluated based on radiological findings. Medical information and demographic data were obtained from survey records. Multivariate regression analysis was performed to investigate the relationship between knee osteoarthritis and metabolic syndrome, and the number of metabolic syndrome components for dose-response relationship evaluation. Analyses were adjusted by age group (model 1) or by age group, education, smoking, alcohol consumption, and physical activity (model 2). Results: A total of 8,491 subjects (3,684 men and 4,807 women) were included in the study. In women, metabolic syndrome increased the risk of knee osteoarthritis (odds ratio (OR) = 1.644, p < 0.001; and OR = 1.608, p < 0.001; respectively; for models 1 and 2) and severe knee osteoarthritis (OR = 1.593, p <0.001; and OR = 1.559, p < 0.001; respectively; for models 1 and 2). However, in men, knee osteoarthritis and severe knee osteoarthritis were not associated with metabolic syndrome. As the number of metabolic syndrome components increased, knee osteoarthritis and severe knee osteoarthritis generally increased in women, but not in men. Conclusion: Metabolic syndrome affects the development of knee osteoarthritis and severe knee osteoarthritis in women. In addition, dose-response relationships were observed between metabolic syndrome components and knee osteoarthritis in women, but not in men.